Studi Genetik Ternak Lokal Indonesia untuk Pelestarian Plasma Nutfah Nasional - Karyadi Munib (Lembaga Penelitian dan Pendidikan (LPP) Kalibra, 2025)
Indonesia is home to diverse local livestock populations that possess unique genetic characteristics and strong adaptation to tropical environments. However, increasing industrialization, uncontrolled crossbreeding, declining effective population size, and the absence of a comprehensive national genomic database threaten their sustainability. This study aims to examine genetic diversity, population structure, and conservation priorities of Indonesian local livestock using molecular markers including microsatellites, mtDNA, SNPs, and whole-genome sequencing. A literature-based analytical approach was used to synthesize findings from recent genetic studies on cattle, buffalo, goats, sheep, and poultry. Results indicate that local breeds such as Bali cattle, Madura cattle, Kacang goats, and Pelung chickens retain high within-population genetic diversity and signatures of selection linked to heat tolerance, parasite resistance, and efficient metabolism. However, introgression from imported breeds has reduced genetic purity in several populations. The findings highlight the urgent need for integrated conservation strategies, including genomic-assisted breeding, establishment of a national genetic repository, and community-based in situ protection. Overall, this study underscores the strategic role of genetic research in preserving Indonesia’s livestock biodiversity and strengthening sustainable breeding programs.